Developing Tactile Maps for Students with Visual Impairments: A Case Study for Customizing Accommodations. (March 2018) - Feucht, Florian C.; Holmgren, Chelsea R.
Introduction: The authors of this study evaluated the necessary features of tactile maps to provide independent, efficient, and safe travel across a university campus; and a process for developing tactile maps based on user needs and preferences. Methods: Participants who have low vision provided input, through interviews and field tests, regarding which features were critical for a tactile map. The four-phase development and research design process included: phase 1, semi-structured interviews about campus navigation; phase 2, creating draft maps using two different tactile media—microcapsule or braille embossed lines; phase 3, field-testing maps through site visits with participants; and phase 4, finalizing the map. Four undergraduate students with low vision participated in phases 1 and 3 to assess their experiences in navigating a campus; and the collected data were used in phases 2 and 4 to create, revise, and finalize the content, layout, and medium of the map. Results: Three of the participants preferred microcapsule lines to braille embossed fines, while one participant stated the usefulness of both media. The four-phase process allowed customization of local maps for individual users. Discussion: Map features that contribute to readability and efficacy of use include the medium; the layout; the combination of orientation maps, which provide an "overview" of a large area; and mobility maps, which contain more detail and are designed to help the traveler in unfamiliar areas (James, 1982). Implications for practitioners: Colleges and universities should gather data and create tactile campus maps for students with low vision or blindness following the four-phase process used during this study. Although the data show that the map's medium is a matter of personal preference, several features are essential to creating a map with maximum readability.